Transparent Things: A Cabinet - Williams, Maggie M.; Overbey, Karen Eileen (Punctum Books, 2013)
"Inspired by a passage in Vladmir Nabokov's Transparent Things (1972), and also compiled as a future love letter to The Material Collective, the essays collected here play with the transparency of pedagogy, scholarship, and writing, as well as with objects that can be seen through, such as crystals and stained glass... In her essay, "Encountering the Inauthenthic," Jennifer Borland investigates how we negotiate our material objects of study and their phenomenological effects when they aren't there at all, when they are technically absent -- in an inaccessible place [such as the British Library], distant from the classroom, or present only in "medievalistic" reproductions and re-creations, such as the building of the Ozark Medieval Fortress in Lead Hill, Arkansas [projected completion date: 2030], or by participating in a workshop on making manuscripts using medieval materials and techniques. As Borland argues, first-hand experience of these re-creations can be used, as Christopher Tilley has also argued, "to gain access to the experience of other persons," including those who lived in the past who are seemingly forever cut off from us. For Borland then, better understanding the past is partly a lived, phenomenological, and shared experience that resides in the body in "touch" with certain objects and processes of making objects. This experience, of course, is also partly indescribable and words are not always adequate to its "occasions," and Borland wonders if there might be new scholarly-phenomenological modes, especially in the digital age, that might allow us to "move beyond language," in order to better render how the object serves as the "meeting place" various types of encounters across time. In "Touched for the Very First Time: Losing My Manuscript Virginity," Angela Bennett-Segler describes, in the style of an exhibitionist, her first "physical" encounter with medieval manuscripts in the Bodleian Library, where the touch of a codex "occupies the cohabitation of languages -- or signifying economies -- in a side-by-side existence that is a condition of the experience of jouissance," and where scholarly objectivity is dissolved "into the anonymity of the particpatory community" enclosed in medieval manuscripts. In "Close Encounters with Luminous Objects: Reflections on Studying Stained Glass" [from which essay we culled the image for the cover of the book], Nancy Thompson asks how we can "translate" the often exhilarating first encounters with medieval objects (such as stained-glass windows in medieval cathedrals) into our more dryly-conceptalized scholarly apparatus, which often seems to lead away from the objects that draw us to the study of art history to begin with? How might we reckon with the metaphysical aspects of studying art history: is this a spiritual exercise as much as a scholarly-historical one?" -- Publisher description.